"No one should be alone in living this process": trajectories, experiences and user's perceptions about quality of abortion care in a telehealth service in Chile. Issue 3 (10th January 2022) - Larrea, Sara; Hidalgo, Camila; Jacques-Aviñó, Constanza; Borrell, Carme; Palència, Laia
Abstract: Self-managed abortion is a common self-care practice that enables pregnant people to exercise their rights to health, bodily autonomy and to benefit from the advances of science even when living in contexts that do not guarantee these rights. In this interpretative qualitative study, we aimed to understand women's abortion trajectories, experiences with self-managed abortion and assessments of the quality of care provided by Women Help Women (WHW, an international activist non-profit organisation working on abortion access). Grounded in feminist epistemology and health inequalities approaches, we conducted eleven semi-structured interviews in Santiago, Chile. We found that illegality, stigma and expectations surrounding motherhood and abortion determined women's experiences. Participants perceived the WHW service as good, trustworthy, fast and affordable, and valued confidentiality and privacy; the quantity and quality of information; having direct, personalised and timely communication with service staff; being treated with respect; and feeling safe, cared for and supported in their decisions. Most participants considered self-managed abortion appropriate and acceptable given their circumstances. Fear was the dominant feeling in women's narratives. Some participants mentioned missing instant communication, in-person support and professional care. We conclude that support, information and company are key to improving abortion seekers' experiences and enabling their decisions, particularly in legally restrictive settings. Centring care in pregnant people's needs and autonomy is fundamental to ensure safe, appropriate and accessible self-care interventions in reproductive health. Social and legal changes, such as public funding for abortion, destigmatisation and decriminalisation, are needed to realise people's right to higher standards of healthcare.